The psychiatric context of the culturally motivated crime - Rinoldi, Pietro Olmo; Borgo, Melania (Medicina Historica, 2017)
This paper aims to consider the conceptual context in which psychiatry is situated when it faces to culturally oriented offense, as in the case of psychiatric evaluation as part of the criminal trial. The starting point of the psychiatric science is the concept of normality and his goal is to analyze and classify patterns of behavior. It is an historical concept (in time and space) and, as such, strongly conditioned by culture, customs and, nonetheless, traditions. Globalization -whose indicator is the widespread mobility of people in space- determines many problems when it comes to define the content of normal behavior, especially when we try to compare the content of prevalent behavior with behavior patterns of people belonging to cultural minorities.